Office systems : proceedings of the IFIP TC 8 Working Conference on Office Systems, Helsinki, Finland, 29 September-2 October 1985 - IFIP TC 8 Working Conference on Office Systems (1985 : Helsinki, Finland); Verrijn-Stuart, Alex; Hirschheim, Rudy A.; International Federation for Information Processing. Technical Committee for Information Systems (Amsterdam ; New York : North-Holland ; New York, N.Y., U.S.A. : Sole distributors for the U.S.A. and Canada, Elsevier Science Pub. Co., 1986)
Includes bibliographies.